Development of pharmacy activity in Serbia - what do we need? - Andjelković, Jasna; Milijić Petrović, Valentina; Marković , Mirjana; Palović, Dragana; Buha Djordjević , Aleksandra; Popović , Ivana; Stojkov, Svetlana; Gigov, Slobodan; Drenić, Dušan (Archives of Pharmacy, 2022)
This paper presents a set of recommendations that can contribute to the improvement of the pharmacy business. They resulted from a series of professional meetings and a collection of opinions from masters of pharmacy employed in various health care institutions in the Republic of Serbia. The general recommendation would imply strict compliance with existing laws (Law on Medicines and Medical Devices (1), Law on Health Care (2)), but also the adoption of the Law on Pharmacy, following the example of countries with developed pharmacy practice. Individual key provisions that would bring improvement of pharmacy and quality pharmaceutical services to patients in the short term are the mandatory presence of at least one licensed pharmacist during the entire working hours in each pharmacy, as well as compliance and control of prescription and over-the-counter medicines. In the long term, strengthening national regulatory bodies in the field of medicines and medical devices is important for improving the quality, safety, and efficacy of medicines and the issuance and application of therapy. According to all standards, these jobs should be entrusted exclusively to masters of pharmacy, and in certain cases to appropriate pharmacy specialists. Development of specific clinical skills and introduction of additional services, such as vaccination and disposal of pharmaceutical waste, would significantly contribute to resource savings and contribute to the health system.